2003
DOI: 10.1080/13698570310001606950
|View full text |Cite
|
Sign up to set email alerts
|

Achieving compliance in chronic illness management: illustrations of trust relationships between physicians and nutrition clinic patients

Abstract: This paper presents empirical research from a study of trust and co-operation between chronic illness patients and their physicians, conducted in nutrition clinics. The paper details models of trust and co-operative behaviour designed to aid interpretive analysis. The paper then presents an interpretive discussion of 16 examples from interactions observed between patients and their consultants at the initial visit and revisit stage of the illness management process in consecutive clinics. This illustrates some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…It is also crucial to patient readiness to seek healthcare, divulge sensitive information and adhere to physicians' advice (Hall et al, 2001). Studies have explored the influence of trust on the patient-physician relationship in terms of modulating different aspects of the therapeutic processes such as the willingness of health care seekers to endorse the physician's recommended treatment has been reported to be associated with statistically significantly higher level of trust (Collins et al, 2002;Dibben and Lena, 2002). Different authors have also reported positive associations between trust and treatment adherence (Joos et al, 1996;Thom et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is also crucial to patient readiness to seek healthcare, divulge sensitive information and adhere to physicians' advice (Hall et al, 2001). Studies have explored the influence of trust on the patient-physician relationship in terms of modulating different aspects of the therapeutic processes such as the willingness of health care seekers to endorse the physician's recommended treatment has been reported to be associated with statistically significantly higher level of trust (Collins et al, 2002;Dibben and Lena, 2002). Different authors have also reported positive associations between trust and treatment adherence (Joos et al, 1996;Thom et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Trust has been recognised as particularly significant for effective healthcare provision across many national systems and provider contexts (Mechanic, 2001;Dibben and Lena, 2003;van der Schee et al, 2007) and moreover as incorporating a number of different dimensions such as macro-level policies, inter-professional cooperation and professional/patient communication (Calnan and Sanford, 2004). Trust relations are significant in shaping and facilitating interactions and transactions between patients and professionals (see Mechanic and Meyer, 2000), but, as a limited amount of research has highlighted, also amongst doctors and between healthcare professionals and managers (Gilson et al 2005;Brown et al 2011).…”
Section: Sociological Narratives Of Trust: An Overviewmentioning
confidence: 99%
“…Trust is recognised as significant for providing effective healthcare across national systems and provider contexts (13,14,15). Rowe and Calnan (16) contend that "the cost of failing to recognise the importance of trust and to address the changing nature of trust relations could be substantial: economically, politically, and most important of all, in terms of health outcomes" (p.6).…”
Section: Trust and Its Importance In The Health Systemmentioning
confidence: 99%